INTERNALISASI NILAI PENDIDIKAN AGAMA HINDU PADA GENERASI Z DI ERA DISRUPSI DIGITAL: ANTARA SPIRITUALITAS DAN BUDAYA VIRTUAL - Ni Kadek Puspita Sari (Yayasan Pendidikan Literasi Borneo, 2026)
This study aims to analyze the internalization of Hindu Religious Education values among Generation Z in the era of digital disruption. The research employed a qualitative approach using a hermeneutic phenomenological design and cyber ethnography (netnography). Data were collected through observation, in-depth interviews, documentation, and analysis of Generation Z Hindu digital activities in virtual spaces. Data analysis was conducted inductively through data reduction, categorization, interpretation, and conclusion drawing. The findings show that digital media has become a new space for the internalization of Hindu Religious Education values. Generation Z tends to gain religious understanding through social media and digital platforms that are visual, interactive, and practical. This condition provides positive impacts in the form of easier access to Hindu religious knowledge, but it also creates challenges such as the superficiality of spirituality and religious image-building culture on social media. Values such as Tri Kaya Parisudha, Tat Twam Asi, and Karma Phala remain relevant as the foundation of digital ethics and responsible online behavior. This study also formulates the concept of “Hindu Virtual Spirituality” as an integration of Hindu spiritual values with modern digital culture.